2019
DOI: 10.5897/ajb2018.16539
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype analysis of Ethiopian bread wheat (Triticum aestivum) cultivars and elite lines for yellow rust resistance genes using linked molecular markers

Abstract: Yellow rust, caused by Puccinia striiformis f. sp. tritici, is one of the most important diseases of wheat in Ethiopia. Poor knowledge of resistance genes deployed in Ethiopian wheat cultivars is one major factor for recurrent epidemics of rust diseases. Molecular marker based gene identification showed the presence of Yr1,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…tritici populations is mainly due to the long-distance migration, high mutation, somatic recombination, and selection of the cultivars (Wan et al, 2004;Chen, 2005 Yr3a, Yr3b, Yr4a, Yr6, Yr6+2, Yr7, Yr8, Yr9, Yr9+2, Yr10, Yr17, Yr24, Yr27, Yr32, YrA, YrCV, YrSD and YrSU, has been reported worldwide, including Egypt (Dawit et al, 2012;Shahin, 2017;Draz, 2019). Dawit et al (2019) found that the differential lines carrying Yr9, Yr8, Yr6 and Yr7 had the highest rust severity of more than 80 S. Nazari and EL Amil (2013) reported that NILs Yr6, Yr7, and Yr9 responded with high infection types. The Yr9 was found among genes that are susceptible to 70-100% of sixty-one isolates of P. striiformis f. sp.…”
Section: Discussionmentioning
confidence: 99%
“…tritici populations is mainly due to the long-distance migration, high mutation, somatic recombination, and selection of the cultivars (Wan et al, 2004;Chen, 2005 Yr3a, Yr3b, Yr4a, Yr6, Yr6+2, Yr7, Yr8, Yr9, Yr9+2, Yr10, Yr17, Yr24, Yr27, Yr32, YrA, YrCV, YrSD and YrSU, has been reported worldwide, including Egypt (Dawit et al, 2012;Shahin, 2017;Draz, 2019). Dawit et al (2019) found that the differential lines carrying Yr9, Yr8, Yr6 and Yr7 had the highest rust severity of more than 80 S. Nazari and EL Amil (2013) reported that NILs Yr6, Yr7, and Yr9 responded with high infection types. The Yr9 was found among genes that are susceptible to 70-100% of sixty-one isolates of P. striiformis f. sp.…”
Section: Discussionmentioning
confidence: 99%